Parallel computation for three-dimensional shell analysis of curved configuration based on domain decomposition method - Joo, HyunShig; Cho, Haeseong; Kim, Seil; Shin, SangJoon; Kwak, JunYoung (Journal of computational science, 2018)
•A parallel computational algorithm is developed based on FETI method with localized Lagrange multipliers.•The curved configuration ofthree-dimensional structures isconsidered by introducing rotational operators.•Practical performance of proposed algorithm is evaluated through static and dynamic analysis using message passing interface (MPI). In this paper, a parallel computational algorithm is developed based on finite element tearing and interconnecting (FETI) method, specifically, localized Lagrange multipliers. The proposed FETI method decomposes large-size structures into non-overlapping subdomains via localized Lagrange multipliers. To consider the curved configuration of large-size structures, a facet shell element created by combining an optimal triangle membrane and discrete Kirchhoff triangle bending plate (OPT-DKT) is suggested and used by introducing rotational operators. Moreover, practical performance of the present OPT-DKT facet shell element is evaluated through static and dynamic analysis. Finally, parallel computation is implemented for the proposed approach using message passing interface (MPI).